IMPLEMENTATION OF “TRIPLE HELIX+” CONCEPT FOR CHANGE MANAGEMENT IN HIGH-EDUCATION SYSTEM - Babichev A.V. (Pressing Problems of Public Administration, 2017)
The article deals with the concept of “Triple Helix”, which determines the interaction between higher educational institutions, authorities and business, and its development into the concept of “Triple helix +”, in which the public is added to these components. The introduction of this concept for managing changes in the system of higher education is considered. It is determined that the formation of “Triple Helix+” involves two main stages. The  rst stage is the creation of a single common space. At this stage, there is a transition from non-interference model to balanced model. In practice, the contribution of the four components of the “Triple Helix+” may more or less differ due to the different degree of involvement of these components. The second stage is the differentiation of the common space. This stage involves the division of a common space into three: the space of knowledge, the space of cooperation, the space of change. This differentiation is achieved through the mobilization of speci c actors, relationships and resources, and the creation of new institutional formats under the in uence of speci c local or regional needs, features of the components of the Triple Helix + and their environment.